Panel Estimating Effects of Macroeconomic Determinants on Tax Revenue Level in European Union - Kalaš, Branimir; Đurović Todorović, Jadranka; Đorđević, Marina (Industrija, 2020)
The level of tax revenue represents one of the most important issue for every country, especially in extraordinary circumstances.  The aim of this paper is to identify which macroeconomic determinants are important to total tax revenue in order to determine which variables are the key generators of tax revenue collection. The subject of this research represents the estimating effects of selected macroeconomic determinants on total tax revenue in European Union countries from 2006 to 2018. Empirical analysis includes three panel regression models where total tax revenue, direct tax revenue and indirect tax revenue are determined as dependent variables. Results of fixed effects model show that 1% increase of GDP enhances total tax revenue for 6.91%. Government expenditure, total investment and population have positive effect on total tax revenue where 1% increase of these determinants raise total tax revenue for 2.38%, 0.001% and 0.57% in these countries. Contrary, inflation, unemployment and gross national savings negatively affect the total tax revenue where their growth by 1% cause lower level of total tax revenue for 3.72%, 0.001% and 1.48%. Likewise, gross domestic product and total investment lead to greater change of direct tax revenue and indirect tax revenue. Empirical findings show that governments in EU countries should focus to higher GDP growth rate, greater level of government expenditure and total investment to enhance the total tax revenue level.
Keywords: taxes, macroeconomic determinants, European Union, panel data estimation